Regional and local identity in built environment and material culture as important part of social and cultural sustainability and wellbeing (2019)
Paper deals regional identity as crucial part of as part of environmental assessment within social and cultural sustainability. In the contemporary era of globalisation and unification in material culture, it is very important to maintain and apply elements and concepts that are special and unique for single localities and regions. Cultural identity and tradition are inseparable parts of every society and can influence the character of local built-environment and its elements. This “DNA” of society indirectly affects the typology/morphology and semiotics of crafted products and architecture, and it creates the basics of the design language of a country or region. Local identity can be understood as the essence of a cultural heritage and genius loci and plays a very important part in self-identification. This is unfortunately very often misinterpreted in the design of contemporary building or products. Although there exist many research studies in field of ethnography, cultural anthropology, history and archaeology, they are very rarely available and understandable for architects, designers, investors, producers and services providers directly in the regions. Maintaining the social and cultural sustainability through maintaining and creating local identity in the built environment and in the life style - this means to bring back local materials, principles, concepts, stories into material culture – architecture, housing, habits, performance in daily life, connected with using of products. Preserving local identity is a big challenge also for local industry and can be massively supported by new forms of responsible and sustainable tourism, thus it has to be experienced, explored and shared, to be alive. Here we can speak about potential of agroturism, eco-tourism, etnoturism that need also infrastructure with its built environment and its elements – products to use during the experience or to bring home for reminding and to display, connected also with attachment to some objects. Paper shows examples how to preserve the regional and local identity, transform, interpret it and to refer to it on the first results of project IDENTITY SK - common platform of design, architecture and the social sciences, in form of regional concepts for products and services, coming from interdisciplinary literature and field research and storytelling. First of all it is necessary to research about it, respect it, having a lot of respect and empathy by adding something new, use it with the context and telling stories, not to embed in misinterpretation and be stranded in many form of kitsch..